Algebra 1: Common Core (15th Edition)

Published by Prentice Hall
ISBN 10: 0133281140
ISBN 13: 978-0-13328-114-9

Chapter 4 - An Introduction to Functions - 4-7 Arithmetic Sequences - Practice and Problem-Solving Exercises: 43

Answer

A(n) = A(n - 1) - 5 ; A(1) = 3

Work Step by Step

The formula for a recursive expression is A(n) = (n - 1) + c (c represents the common difference) All of the missing pieces in this equation are provided in the explicit equation in the question where the c value is the d value in the explicit equation and A(1) is listed before (n - 1). C = -5 A(1) = 3 After we plug this in the explicit expression, we get the formula A(n) = A(n - 1) - 5 ; A(1) = 3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.